Incidence of Hard Tissue Disease on Periapical Radiographic Examination at Prima Oral Dental Hospital Medan Indonesia - Andre Yonathan Purba; Mellisa Sim; Putra, Phimatra Jaya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Caries is a chronic infection of dental hard tissue. The development of caries is not limited to the tooth area, but caries can progress to the pulp chamber resulting in periapical lesions and abnormalities if not treated. Early detection of oral disease through radiographic examination is important, one of which is through periapical radiography. Methods. This type of research is descriptive. The sample of this research is periapical radiography of cases of hard tissue disease at Prima Oral Dental Hospital period April – May 2021 as many as 78 photos. Sampling in this study was done by random sampling. Data were analyzed descriptively. Results. Based on the interpretation of 78 photos periapical radiographs, it was found that the highest number of caries cases at Prima Oral Dental Hospital was superficial caries as much as 48.7%, followed by media caries as much as 43.6% and profunda caries only 7.7%. The mean and standard deviation of superficial caries depth was 3.51±1.348; medium caries 6.88±1.122 and profunda caries 10.00±1.549. Conclusion. Superficial caries is the most caries case found on periapical radiographic examination at Prima Oral Dental Hospital, while profunda caries is the least caries case.